Adeno-associated virus gene therapy vector scAAVIGF-I for transduction of equine articular chondrocytes and RNA-seq analysis. Issue 5 (May 2016) - Hemphill, D.D.; McIlwraith, C.W.; Slayden, R.A.; Samulski, R.J.; Goodrich, L.R.
Summary: Objective: IGF-I is one of several anabolic factors being investigated for the treatment of osteoarthritis (OA). Due to the short biological half-life, extended administration is required for more robust cartilage healing. Here we create a self-complimentary adeno-associated virus (AAV) gene therapy vector utilizing the transgene for IGF-I. Design: Various biochemical assays were performed to investigate the cellular response to scAAVIGF-I treatment vs an scAAVGFP positive transduction control and a negative for transduction control culture. RNA-sequencing analysis was also performed to establish a differential regulation profile of scAAVIGF-I transduced chondrocytes. Results: Biochemical analyses indicated an average media IGF-I concentration of 608 ng/ml in the scAAVIGF-I transduced chondrocytes. This increase in IGF-I led to increased expression of collagen type II and aggrecan and increased protein concentrations of cellular collagen type II and media glycosaminoglycan vs both controls. RNA-seq revealed a global regulatory pattern consisting of 113 differentially regulated GO categories including those for chondrocyte and cartilage development and regulation of apoptosis. Conclusions: This research substantiates that scAAVIGF-I gene therapy vector increased production of IGF-I to clinically relevant levels with a biological response by chondrocytes conducive to increased cartilage healing. The RNA-seq further established a set of differentially expressed genes and gene ontologies induced by the scAAVIGF-I vector while controlling for AAV infection. This dataset provides a static representation of the cellular transcriptome that, while only consisting of one time point, will allow for further gene expression analyses to compare additional cartilage healing therapeutics or a transient cellular response.